2019
DOI: 10.3389/fphys.2019.01231
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Spatial Mapping of Muscle Synergies in Highly Variable Upper-Limb Movements of Healthy Subjects

Abstract: BackgroundRecently, muscle synergy analysis has become a standard methodology for extracting coordination patterns from electromyographic (EMG) signals, and for the evaluation of motor control strategies in many contexts. Most previous studies have characterized upper-limb muscle synergies across a limited set of reaching movements. With the aim of future uses in motor control, rehabilitation and other fields, this study provides a comprehensive characterization of muscle synergies in a large set of upper-limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(122 citation statements)
references
References 53 publications
5
101
2
Order By: Relevance
“…These challenges have only been partially addressed in literature. The effect of some of these sources of variability on extracted muscle synergies was already emphasized in several studies on healthy people, when assessing upper-limb intra-and inter-subject synergy composition similarity [5,21,22] or gait variability [23]. Several studies tried to quantify variability in various conditions, even in hardly comparable designs and topics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges have only been partially addressed in literature. The effect of some of these sources of variability on extracted muscle synergies was already emphasized in several studies on healthy people, when assessing upper-limb intra-and inter-subject synergy composition similarity [5,21,22] or gait variability [23]. Several studies tried to quantify variability in various conditions, even in hardly comparable designs and topics.…”
Section: Introductionmentioning
confidence: 99%
“…These studies conclude that, in general, variability is found intra-session and intra-subject as well as inter-subject. However, much can be done to assess these sources of variability in more detail [5,20,22]. In the case of patient evaluations, it is expected that this variability is found as well and is even more prominent, since in general, neurological patient movements have a lower repeatability and larger heterogeneity at the kinematic and EMG level than those of healthy people [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated shared or merged muscle synergies across different tasks such as walking and running 8,42 , walking and cycling 25 , various directions of reaching 14,32 and stepping and non-stepping postural controls 35 . Their results indicated that different human behaviors use the fundamental motor modules that reflect the functional control units as a neural constraint on motor outputs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding seems to point at a more flexible character of the linking of DOF in synergies, which is in line with several papers demonstrating that muscle synergies differed across task constraints cf. 39,53,54,5963 . An alternative perspective suggests that the large base of movements can generally characterised as the combination of dynamic primitives 64 .…”
Section: Discussionmentioning
confidence: 99%